(untitled) (Ibrahim Cardiac Medical Journal, 2020)
Background & Objective: Intertrochanteric femur fractures are becoming increasingly common as our population ages. Effective treatment strategies that result in high rates of union of these fractures and low rates of complication are important. This study was designed to evaluate the clinical outcome of intertrochanteric fracture treated with dynamic hip screw, among many other fixation techniques available to fix intertrochanteric fractures. Methods: This prospective interventional study was done in the Department of Orthopaedics & Traumatology Department of Dhaka Medical College Hospital, Dhaka between June 2013 to November 2014. A total of 30 patients having intertrochanteric femur fracture were treated with Dynamic Hip Screw (DHS) after doing all necessary investigations for anesthetic fitness. Regular follow up was done up to six months after each operation and was observed for fracture healing, stability, complications and functional outcome by the prescribed scoring system (Harris Hip Score). Result: Nearly one third (30.0%) of the patients belonged to 7th decade and male to female ratio was 1:1.3. According to Harris Hip Score, 13(44.82%) patients were rated as excellent, 9 (31.03%) good, 5(17.24%) fair and 2(6.89%) poor. Conclusion: Dynamic hip screw (DHS) is a reliable method of fixing the stable intertrochanteric femur fractures. The reliability and long-term effect of dynamic hip screw used to treat intertrochanteric fractures of unstable variety are unsatisfactory and not up to the mark. Ibrahim Card Med J 2019; 9 (1&2): 36-41